Acellular dermal matrix in urethral reconstruction - Aodi, Jiang; Ying, Lian; Chengyang, Sun; Hongfeng, Zhai (Frontiers in Pediatrics, 2024)
The management of severe urethral stricture has always posed a formidable challenge.Traditional approaches such as skin flaps, mucosal grafts, and urethroplasty may not be suitable for lengthy and intricate strictures. In the past two decades, tissue engineering solutions utilizing acellular dermal matrix have emerged as potential alternatives. Acellular dermal matrix (ADM) is a non-immunogenic biological collagen scaffold that has demonstrated its ability to induce layer-by-layer tissue regeneration. The application of ADM in urethral reconstruction through tissue engineering has become a practical endeavor. This article provides an overview of the preparation, characteristics, advantages, and disadvantages of ADM along with its utilization in urethral reconstruction via tissue engineering.